Zonificación ambiental para el Plan de Manejo Ambiental Microcuenca Río Chipatá – Quebrada Uval, en el municipio de Guasca, Cundinamarca (2022)
In Colombia, At the moment, hydrographic basin units are currently defined that allow a responsible and adequate use of resources, these areas must be aligned with the regulation, the management plans and the areas declared as protected. Rivier Chipatá -Uval micro-basin is located in the municipality of Guasca Cundinamarca, which belongs to the Bogotá River Basin. In this project, an environmental zoning is proposed within the Environmental Management Plan of the micro-basin, which regulates, proposes and articulates in the best way the study area in the process of protecting the ecosystem and restoring the areas that are being violated. base and thematic secondary information, satellite images and processing, aligned and defined taking into account the categories defined in Decree 2372 of 2010. Using current land use coverage information, potential use, identifying protection areas and different parameters , to define an environmental zoning proposal that allows an adequate management of natural resources, keeping in mind the anthropic activity and its respect for sustainable development. At the end, 3 main classes were defined: Zone of left that indicates the continuous management of protected areas with an extension of 1855 hectares, being 85% of the microbasin, present restoration area that indicates a protection area that is used by different actors inadequately and must be restored, which corresponds to 5% being a total of 108 hectares, and finally the area of sustainable use, a component for areas of anthropogenic use such as crops, pastures and for other economic activities, with an extension of 220.93 hectares representing 10% of the micro-basin